UJI TINGKAT KEAWETAN TELUR AYAM TERHADAP BAHAN PERENDAMAN - Agustina Widyasworo; Risma Novela Esti (AVES: Jurnal Ilmu Peternakan, 2022)
This study was carried out in the laboratory of the Faculty of Animal Husbandry, Balitar Islamic University, since 1 July 2022 until 21 July 2022. This study aimed to determine the concentration of guava leaves and coconut coir extract to maintain the quality of egg. The materials used in this research were eggs, hot water, guava leaves and coconut coir. Eggs are soaked for 1 days (24 hour) with concentration of guava leaves consists of 12%, 18%, and 24%, coconut coir consists 30%, 40%, and 50% and stored for 21 days. Parameters observed were egg weight reduction, yolk index, albumen index and haugh unit. The experiment designed by Completely Randomized Design (CRD) with 6 treatments and 3 replications. Parameters observed were egg weight shrinkage, yolk index, eggwhite index and haugh unit. The data were analyzed by ANOVA continued by Least Significance Different (LSD). The results of analysis of variance showed that soaking eggs using guava leaves and coconut coir extract had no significant effect (P>0,05) on egg yolk index, egg white index, and egg weight reduction. The research results showed that interior quality of eggs was higher in the guava leaves (18%) treatment. The conclusion from the results of this study is that the concentration of 18% and the soaking time of 24 hours gave good results on the haugh unit